PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SAVI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII MTs. NURUL WATHAN PLAMBIK - Haniifan Musliman; Sutarto Sutarto; Zainal Abidin; Intan Dwi Hastuti (Yayasan Pendidikan Intan Cendekia, 2018)
Based on the observations of students of class VII in MTs. Nurul Wathan Plambik found that the subject of mathematics is a lesson that is considered relatively difficult. Thus an alternative method is needed to improve student learning outcomes. One of them is by applying cooperative learning model of SAVI type (Somatic, Auditory Visual, Intellectual) This learning model is applied with the aim to describe the learning outcomes on the subject matter of integers.This research is a type of classroom action research conducted in 2 cycles, each cycle consists of five stages of planning, implementation, observation, evaluation, and reflection Based on the data analysis shows the results of observation and evaluation that the students' learning outcomes in the cycle obtained the average value of students 70.89 with the highest score of 87 and the lowest value 30 with the percentage of class 75% , it can be seen that the percentage of students' learning mastery on us I has not met the criteria set at 2 85%, and the increase in the average score of students is 77.86 with the highest score 90 and the low grade 43 with 89% classical completeness. research can be concluded that application of learner model an cooperative type SAVI can improve student learning outcomes in the matter of integers in class VII MTs Nurul Wathan Plambik academic year 2017/2018.